Filosofskoe razmyšlenie o fenomene odinočestva - Turarov, S. (Chabaršy. Dintanu serijasy, 2023)
How often do we try to avoid things that help us survive. People have been trying for centuries to avoid loneliness or get used to it. The Cursed loneliness, the resigned unnoticed, the wise with pleasure. Loneliness is always there, so we need it. You feel lonely both in solitude and among a large number of people. The feeling of loneliness depends on the structure of the personality. Another factor, the unsatisfactory situation of demographic numbers needs solutions - loneliness Is a more attractive trend nowadays, it changes the established structure of values and relationships of humans, therefore it requires a clear identification of the axiological status of the given phenomenon, as well as its positive and negative features. The solutions of all the named problems are prevented by the insufficiency of a general theoretical approach to understand loneliness. The problem of loneliness constantly concerns humanity, covering the minds of philosophers, writers, scientists. Recently, more and more works have been devoted to the problem of loneliness, studying the causes of loneliness, its essence, characteristic manifestations and influence on different categories of people at different stages of life. However, at the moment there is no consensus on what loneliness is: trouble or happiness, the norm or pathology. The degree of development of the problem. Western social science, which has been dealing with the problem of loneliness for several decades, has developed many approaches to its study. Philosophical, psychological, sociological literature is found in a large number in the corpus of scientific work on this issue. Most of them were published in the last decades of the 20th century, but most of them are small articles, often of a popular science nature, or fragmentary reviews.